PERSEPSI MAHASISWA TERHADAP EFEKTIVITAS PENGGUNAAN - Lanang Diayudha (Business Management Journal, 2017)
The purpose of this survey is to find out the effectiveness of UBM shuttle buses. This is a quistionaire-based survey with 100 respondents that is purposively selected. Data analysis uses mean and validity and realibility for questionnaire produce the following results: the UBM shuttle buses is the facility used by the UBM students, that economically help the students expenses.  Key Words:Student perception, effectivity, UBM shuttle bus